The Mechanism and Management of Adverse Cardiac Reactions Induced by Immune Checkpoint Inhibitors Therapy - Fangning Rong; Kangting Ji; Yingpei Weng; Yangpei Peng (Cardiology Research and Practice)
Immune checkpoint inhibitors (ICIs) therapy has recently been introduced to all kinds of cancers. The adverse reactions associated with this therapy have attracted much attention. The heart-related adverse reactions are mainly the immune-related myocarditis and heart failure. Cases of adverse cardiac reactions caused by ICIs therapy have been clearly reported. However, the pathogenesis of the adverse cardiac reactions remains unclear. Therefore, this article briefly reviews the mechanism and management of adverse cardiac reactions caused by ICIs therapy.